Analisis penyebab dan upaya mitigasi bencana tanah longsor di Desa Semen Kecamatan Gandusari Kabupaten Blitar, Jawa Timur - Septiani, Ariani Candra Dwi (Maliki Interdisciplinary Journal, 2024)
Landslides are one of the natural disasters prone to occur in mountainous areas, especially during the rainy season, which can cause damage to buildings and cause casualties. This research aims to analyze the causes and mitigation efforts of landslides in Semen Village, Gandusari Subdistrict, Blitar District, East Java. Using a descriptive qualitative approach through literature study, this research examines various factors that cause landslides in the area, including rainfall intensity, geological characteristics, and land use. The results showed that in addition to natural factors, there are also human activities that exacerbate the risk of landslides, such as land clearing for agriculture and settlements without considering land management. The proposed landslide mitigation efforts include strong communication between the community and the local government, socialization on landslide understanding, and the active role of the community in forming disaster preparedness groups.